Association of parent-child interactions with parental psychological distress and resilience during the COVID-19 pandemic - Mann, Mana; Harary, David; Louis, Shirley; Wang, Tao; Bonuck, Karen; Isasi, Carmen R.; Charron, Maureen J.; Fuloria, Mamta (Frontiers in Pediatrics, 2023)
The effects of psychological distress/resilience on parent-child engagement (e.g., family dinners, reading) during the COVID-19 pandemic have not been well studied. Among very young children from underrepresented backgrounds enrolled in the ongoing longitudinal Bronx Mother Baby Health Study of healthy term infants, we (1) examined associations between exposures to COVID-19-related events, demographic factors and parental psychological distress and resilience; and (2) correlated these factors with parent-child engagement activities. Between June 2020-August 2021, parents of 105 Bronx Mother Baby Health Study participants aged birth-25 months completed questionnaires related to exposures to COVID-19-related events, frequency of positive parent-child engagement activities, food and housing insecurity, and parental psychological distress and resilience. Families were also asked open ended questions about the pandemic’s impact. 29.8% and 47.6% of parents reported food and housing insecurity, respectively. Greater exposures to COVID-19-related events were associated with increased parental psychological distress. Positive parent-child interactions were associated with demographic factors and higher levels of maternal education, but not with exposures to COVID-19-related events. This study adds to a growing body of literature on the negative impacts of COVID-19 exposures and psychosocial stressors on families during the pandemic, supporting the need for enhanced mental health resources and social supports for families.